1996
DOI: 10.1080/0028825x.1996.10410704
|View full text |Cite
|
Sign up to set email alerts
|

Curling and folding of leaves of monocotyledons — a strategy for structural stiffness

Abstract: Leaves of most monocotyledonous plants gain structural stiffness from curling or folding. This is shown to be true of Phormium spp., where the optimisation seems to be for the leaf to gain as much stiffness as possible by curling longitudinally whilst keeping the maximum amount of projected area available for intercepting light. Smaller plants with less leaf fibre have to fold about the midrib to gain this stiffness, which will reduce their projected area more than curling would but reduces the investment in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 2 publications
2
23
0
Order By: Relevance
“…In recent years, V-shaped, or rolled, leaves were regarded as an important element of the ideal rice plant type (Chen et al 2001). The distinctive shape makes leaves stiVer along the longitudinal axis, thus providing additional support and decreasing droopiness (King et al 1996). Based upon two near isogenic lines (NILs) of the same rice variety with rolledleaf or Xat-leaf characteristics, researchers found that canopy photosynthetic rate, biomass and yield in a rolled-leaf population were higher in medium-and high-density populations, relative to Xat leaf populations.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, V-shaped, or rolled, leaves were regarded as an important element of the ideal rice plant type (Chen et al 2001). The distinctive shape makes leaves stiVer along the longitudinal axis, thus providing additional support and decreasing droopiness (King et al 1996). Based upon two near isogenic lines (NILs) of the same rice variety with rolledleaf or Xat-leaf characteristics, researchers found that canopy photosynthetic rate, biomass and yield in a rolled-leaf population were higher in medium-and high-density populations, relative to Xat leaf populations.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the curvature of the unfolded leaf (app. 71°) that decreases the possible stress (force per unit area) the leaf must resist (King et al 1996), three different types of leaf stiffening concepts were found along the P. tenax leaf: (1) the leaf folding in the basal part (Fig. 1, P1 and P2), (2) the merging of the folded part ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The winding or curling of fresh leaf lamina can be phenotypic characteristic of some modern plant species and seems to represent an adaptation to reduce air movement around under surface of leaves, reducing water loss through less area exposed to direct sun (Abrams, 1990;Phebalium species, Australian National Botanic Gardens, 2000) and/or to gain structural stiffness, maintaining the efficient sun light interception under adverse conditions (for instance, as in species of Phormium, King et al, 1996). However, this feature can be created in some leaves during their decay process after abscission in the litter or on ground surface (= curled dry leaves), or even while still in connection with mother-plant, at some stage in the leaf aging (Xiao and Chen, 2011).…”
Section: Final Remarksmentioning
confidence: 99%